Penerapan Teknologi Pengolahan Citra dalam Analisis Data Visual pada Tinjauan Komprehensif - Supiyandi Supiyandi; Muhammad Abdul Mujib; Khairul Azis; Rahmat Abdillah; Salsa Nabila Iskandar (International Forum of Researchers and Lecturers, 2025)
Image processing has become a key technology in visual data analysis, making significant contributions across various fields such as healthcare, security, and the creative industry. This article provides a comprehensive review of the application of image processing technology in visual data analysis, focusing on the latest methods, tools, and practical applications. We discuss various image processing techniques, including segmentation, edge detection, and pattern recognition, as well as how these techniques are applied to process and analyze visual data. The study also includes performance evaluations of various commonly used image processing algorithms and software. Additionally, we explore the challenges faced in applying this technology, such as image resolution issues, noise, and high computational demands. By offering an extensive overview of the development and implementation of image processing technology, this article aims to be a valuable reference for researchers and practitioners working in the field of visual data analysis.